Parent–Child Relationship Quality and Internet Use in a Developing Country: Adolescents’ Perspectives - Nguyen, Thao Thi Phuong; Nguyen, Tham Thi; Do, Ha Ngoc; Vu, Thao Bich Thi; Vu, Khanh Long; Do, Hoang Minh; Nguyen, Nga Thu Thi; Doan, Linh Phuong; Vu, Giang Thu; Do, Hoa Thi; Nguyen, Son Hoang; Latkin, Carl A.; et al. (Frontiers in Psychology, 2022)
Objective The goal of the study was to explore the relationship between parent–children relationships related to using the internet among kids and potentially associated factors. Materials and Methods A sample of 1.216 Vietnamese students between the ages of 12 and 18 agreed to participate in the cross-sectional online survey. Data collected included socioeconomic characteristics and internet use status of participants, their perceived changes in relationship and communication between parents and children since using the internet, and parental control toward the child’s internet use. An Ordered Logistic Regression was carried out to determine factors associated with parent–children relationship since using the internet. Results The characteristics of the relationship between children and their parents since using the Internet were divided into three levels: deterioration (7.0%), stability (78.2%), and improvement (14.8%). The topics that children most often communicate with their parents include learning, housework, and future directions. Two-way interactive activities, such as supporting parents to use the Internet, have a positive impact on the parent–child relationship. Stubborn parental control, such as establishing rules about contact or allowing Internet access and setting up global positioning system (GPS) to track negatively affecting parent–child relationships. Conclusion Findings indicated that changes in the quality of the parent–child relationship were self-assessed by participants regard to kids’ internet use, especially in the COVID-19 epidemic context. Educational campaigns and programs to raise awareness of parents as to the dangers and negative influences that their children may encounter online, psychology of children’s behaviors and effects of different responding strategies are recommended.